1993
DOI: 10.1148/radiology.187.1.8451413
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage avascular necrosis of the femoral head: MR imaging for prognosis in 31 cases with at least 2 years of follow-up.

Abstract: Thirty-one cases of stage 1 or 2 osteonecrosis (ON) of the hip in 27 patients were studied with T1-weighted coronal magnetic resonance (MR) imaging. Three quantitative parameters were measured on the contiguous MR sections, corresponding to the 2-cm-wide median portion of the femoral head: the angle filled by ON (alpha), the percentage of weight-bearing femoral cortex involved with ON (WB), and the percentage of femoral head surface involved with ON. The clinical and radiologic courses were assessed after at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 0 publications
2
53
0
1
Order By: Relevance
“…Therefore we have tried to assess the prognostic factors for core decompression. Most authors agree that the extent of the necrotic area is closely related to the clinical outcome of osteonecrosis [8,10,13,14,16,18]. However, different methods have been used for measurement of the extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we have tried to assess the prognostic factors for core decompression. Most authors agree that the extent of the necrotic area is closely related to the clinical outcome of osteonecrosis [8,10,13,14,16,18]. However, different methods have been used for measurement of the extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic literature review, Marker et al [12] evaluated the clinical and radiographic outcomes of core decompression in surgeries done before [13][14][15][16][17][18][19][20][21][22] and after 1992 [1,2,10,[23][24][25][26][27][28][29][30][31] (n=1268 and 1337 hips, respectively). The authors demonstrated that in procedures performed before 1992, 41 % of hips required additional surgery after a mean follow-up of 65 months (range, 3 to 216 months).…”
Section: Overall Outcomes Of Traditional Core Decompressionmentioning
confidence: 99%
“…By rotating the femoral head, the diseased weight-bearing surface is reestablished by repositioning the femoral head, reducing the forces on the diseased part to prevent collapse and allow healing [16,28]. Sugioka [28] reported successful outcomes with rotation angles of 55°-70°in anterior rotated TRO and Atsumi and Kuroki [2] reported successful outcomes with rotation angles of up to 180°when performing a TRO with posterior rotation.…”
Section: Discussionmentioning
confidence: 99%